TEACHING GENERAL ENGLISH IN LARGE CLASS SETTINGS: DOES COLLABORATIVE LEARNING METHOD WORK? - Sari, Senorica Yulia; Arianto, M. Affandi (STKIP PGRI Jombang, 2019)
Teaching English as a foreign language has been challenging from time to time. Moreover, dealing with a big number of students in one class will add some displeasure, not to mention various backgrounds of knowledge and gap of English ability that they have. This article aims to see the effectiveness of Colaborative Learning (CL) method in improving students speaking ability and studying behaviour in general English subject in a large classroom context. A classroom action research is used as the experiment method, where post-test and observation sheets happened to be the instruments. The finding of this paper shows that CL successfully promotes an option to improve students' performances, which are spoken ability and studying behavior. Students' attainment in speaking included pronunciation, vocabulary, content accuracy and grammar. Meanwhile, students' attitude that was observed covered enthusiasm, participation, discipline and teamwork.